Electrostatic Potential of Human Immunodeficiency Virus Type 2 and Rhesus Macaque Simian Immunodeficiency Virus Capsid Proteins - Bozek, Katarzyna; Nakayama, Emi E.; Kono, Ken; Shioda, Tatsuo (Frontiers in Microbiology, 2012)
Human immunodeficiency virus type 2 (HIV-2) and simian immunodeficiency virus isolated from a macaque monkey (SIVmac) are assumed to have originated from simian immunodeficiency virus isolated from sooty mangabey (SIVsm). Despite their close similarity in genome structure, HIV-2 and SIVmac show different sensitivities to TRIM5α, a host restriction factor against retroviruses. The replication of HIV-2 strains is potently restricted by rhesus (Rh) monkey TRIM5α, while that of SIVmac strain 239 (SIVmac239) is not. Viral capsid protein is the determinant of this differential sensitivity to TRIM5α, as the HIV-2 mutant carrying SIVmac239 capsid protein evaded Rh TRIM5α-mediated restriction. However, the molecular determinants of this restriction mechanism are unknown. Electrostatic potential on the protein-binding site is one of the properties regulating protein-protein interactions. In this study, we investigated the electrostatic potential on the interaction surface of capsid protein of HIV-2 strain GH123 and SIVmac239. Although HIV-2 GH123 and SIVmac239 capsid proteins share more than 87% amino acid identity, we observed a large difference between the two molecules with the HIV-2 GH123 molecule having predominantly positive and SIVmac239 predominantly negative electrostatic potential on the surface of the loop between α-helices 4 and 5 (L4/5). As L4/5 is one of the major determinants of Rh TRIM5α sensitivity of these viruses, the present results suggest that the binding site of the Rh TRIM5α may show complementarity to the HIV-2 GH123 capsid surface charge distribution.